2015
DOI: 10.7841/ksbbj.2015.30.5.223
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Arrest of Extract from Artemisia annua Linné. Via Akt-mTOR Signaling Pathway in HCT116 Colon Cancer Cells

Abstract: In this study, extract from Artemisia annua in L. (AAE) is known as a medicinal herb that is effective against cancer. The cell cycle is regulated by the activation of cyclindependent kinase (CDK)/cyclin complex. We will focus on regulation of CDK2 by cyclin E. cyclin E is associated with CDK2 to regulate progression from G1 into S phase. Akt is known to play an important role in cell proliferation and cell survival. Activation of Akt increases mTOR activity that promotes cell proliferation and cancer growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…A. annua extracts could contain several molecules, and their composition could be changed not only by the strategy of extraction but also by the time and the place where the plant is harvested [32, 33]. Kim et al [34] evaluated the effect of an A. annua extract on human colon cancer cell line HCT116 and found that cell cycle arrest occurred at the G 1 /S phase mediated by the Akt/mTOR pathway. Later on, they demonstrated that A. annua extract induced apoptosis through the regulation of specific proteins such as Bax, Bak, and cytochrome c in PDK1/Akt signaling pathways via a PTEN/p53-independent manner [35].…”
Section: Discussionmentioning
confidence: 99%
“…A. annua extracts could contain several molecules, and their composition could be changed not only by the strategy of extraction but also by the time and the place where the plant is harvested [32, 33]. Kim et al [34] evaluated the effect of an A. annua extract on human colon cancer cell line HCT116 and found that cell cycle arrest occurred at the G 1 /S phase mediated by the Akt/mTOR pathway. Later on, they demonstrated that A. annua extract induced apoptosis through the regulation of specific proteins such as Bax, Bak, and cytochrome c in PDK1/Akt signaling pathways via a PTEN/p53-independent manner [35].…”
Section: Discussionmentioning
confidence: 99%
“…대장암은 주로 암을 절제하는 외과적 수술로 치료가 이루어지며, 암의 병기(staging)에 따라 항암제 또는 방사선치료가 병행된다. 그러나 이러한 방법은 항암제 내성이 나 면역력 저하와 같은 부작용을 초래한다는 문제점이 있다 [7]. 이러한 이유로 최근에는 천연물 자체의 효능을 기반으로 항암효과가 있는 신규생리활성물질을 개발하기 위하여 많은 연구가 진행되고 있으며, 천연 추출물이 암세포의 성장과 증 식에 관련된 신호전달 분자를 조절함으로써 암을 억제한다는 선행연구들이 보고되고 있다 [11,14,19,20].…”
Section: 서 론unclassified